ANALISIS PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, LIKUIDITAS DAN OPINI AUDIT TERHADAP JANGKA WAKTU PENYELESAIAN AUDIT (AUDIT DELAY) (Studi Empiris pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Ridyan I. Lewen; Maria Douk Tunti (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
This research was conducted on service companies listed on the Indonesia Stock Exchange from 2015-2019. The purpose of thid study was to determine the influence of company size, profitability, solvency, liquidity, and audit opinion on the audit completion period (audit delay) partially and simultaneously on service companies listed on the Indonesia Stock Exchange from 2015-2019. This study uses quantitative methods, namely data obtained from secondary data in the form of annual reports containing a balance sheet, income statement and auditor's statement of opinion. The sample in this study is the annual report of ten service companies listed on the Indonesia Stock Exchange which consistently present their annual reports for five consecutive years, namely 2015-2019. The process of determining the sample in this study used random sampling and purposive sampling methods. The results of the study partially show that company size, profitability, solvency and audit opinion has no effect on audit delay. While liquidity have an effect on audit delay. Simultaneously, company size, profitability, solvency, liquidity and audit opinion have an effect on audit delay.